Kriteria Memilih Pasangan Hidup (Kajian Hermeneutika Hadis) - Najwah, Nurun (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2016)
a saki>nah mawaddah wa rah}mah family is the hope of all married couples. In reality, the rising divorce rate in Indonesia, particularly as recorded by Religious Court, is alarming and thus needs to be studied. There are two main factors that determine the successful marriage: choosing the right spouse-to-be (pre-wedding) and maintaining a good marital relationship (post-wedding). The question to be studied in this article is how the interpretation of hadiths containing teachings on maintaining a good marital relationship using hermeneutics can guarantee its wellbeing.Keywords: Characteristics of the, spouses, saki> nah